Behavioral Engagement Pada Gamifikasi Perkuliahan Daring Pemrograman Visual - Annisa Miranda Permatasari; Saida Ulfa; Dedi Kuswandi; Yerry Soepriyanto (Journal of Educational Technology Studies and Applied Research, 2024)
Visual programming is one of the courses offered in the bachelor's degree in educational technology. Based on a survey in the field, almost 85% of educational technology students do not have a background in learning programming. To provide motivation in learning visual programming, gamification is required in implementation. Usually the gamification principle is held offline. This study aims to determine the behavioral engagement of students during lectures by implementing online gamification. The method used was a survey of 98 students who were taking classes at the 8th meeting. The results showed that empirically the level of student behavioral engagement in visual programming courses was good in the high and medium categories, although some were categorized as low. Hypothetically, students are taking lectures at high and moderate levels. The overall results are discussed in the discussion section of the article.